Issues of Physical Health of Young People (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
this article covers important issues in maintaining public policy regarding the people, first of all, ensuring their healthy lifestyle, maturing them spiritually, intellectually, physically and morally, getting quality education and ensuring wellness and effective use of sports infrastructure.